2015
DOI: 10.1021/acsami.5b06754
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Wetting Hysteresis and Contact Time of a Bouncing Droplet on Hydrophobic Surfaces

Abstract: The contact time of impacting water droplets on superhydrophobic surfaces directly reflects the extent of thermal and energy conversions between the water droplet and the surface, which is also considered to be crucial to the practical applications. The purpose of this study was to reveal the relationship between the contact time and the wetting hysteresis. We designed and fabricated six classes of surfaces with different extent of hydrophobicity through modifying the microscale/nanoscale hierarchical textured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 43 publications
(57 reference statements)
2
52
0
Order By: Relevance
“…In the range of Weber number considered, our results reveal that the drops bounce off the SLIPS even at relatively low We numbers. These results are specific to SLIPS since it is known that water drops do not bounce on surfaces with receding contact angles higher than 100 o as shown by Antonini et al [34,35,36]. Our measurements show that the receding angle for the non-infused surface, θ r = 95 o , does not satisfy this criterion and therefore it explains why the drop does not bounce on such surface.…”
Section: Contact Time Between the Drop And The Surfacesupporting
confidence: 51%
“…In the range of Weber number considered, our results reveal that the drops bounce off the SLIPS even at relatively low We numbers. These results are specific to SLIPS since it is known that water drops do not bounce on surfaces with receding contact angles higher than 100 o as shown by Antonini et al [34,35,36]. Our measurements show that the receding angle for the non-infused surface, θ r = 95 o , does not satisfy this criterion and therefore it explains why the drop does not bounce on such surface.…”
Section: Contact Time Between the Drop And The Surfacesupporting
confidence: 51%
“…Therefore, how to reduce the contact time is significant to anti‐icing, as some researchers found that wetting hysteresis and the solid fraction play significant roles in determining the duration between impacting and bouncing off the substrate . Bird et al used SHS with a morphology to redistribute the liquid mass and reduce the contact time .…”
Section: The Mechanisms Of Anti‐icing and Icephobicitymentioning
confidence: 99%
“…Therefore, how to reduce the contact time is significant to anti-icing, as some researchers found that wetting hysteresis and the solid fraction play significant roles in determining the duration between impacting and bouncing off the substrate. [121,122] [115] Copyright 2002, Nature Publishing Group. B) The impact processes of water droplets on superhydrophobic surfaces with different macrotextures captured by a high-speed camera.…”
Section: Drop Bouncing Mechanismmentioning
confidence: 99%
“…According to the mature Cassie–Baxter wetting theory, the quantity of entrapped air pockets by the surface textures determines the superhydrophobicity, i.e., the APCA and CAH. However, the both wetting parameters are also associated with the work done W against the moving of droplet on solid surface, which can be described by WcosθnormalRcosθnormalA1cosθwhere θ* is the APCA, and θ A and θ R are the advancing contact angle (ACA) and receding contact angle (RCA), respectively, also the difference between θ A and θ R determines CAH. As is well known, the work done W reflects the capacity of impact droplets rebounding off the surface.…”
Section: Resultsmentioning
confidence: 99%